Simulation data for "The Free-Energy Landscape of a Mechanically Bistable DNA Origami" - Wong, C K; Doye, J P K (University of Oxford, 2022)
Simulation data containing the cadnano design files for the systems simulated, the raw data for the free energy landscapes and the final configurations for each umbrella sampling window for each system.